MEASURING THE ASCENDING TREND FOR SUSTAINABLE ENTREPRENEURSHIP: BIBLIOMETRIC ANALYSIS - Plaha, Niraj Gurprakash; Sharma, Pooja (Gadjah Mada International Journal of Business, 2024)
The term Entrepreneurship refers to initiating, organizing, and managing an innovative business to make a profit while winning the financial threat. The concept of Sustainable entrepreneurship has attracted significant scholarly attention over the last decade which states that there is an opportunity for generating new products with new techniques which significantly reduce social and environmental impacts. The study outlines the following research challenges and areas for future study as well as provides bibliometric analyses for the topic of sustainable entrepreneurship. The data shows that throughout time, notably in the last two years, the quantity of publications published and citations has steadily increased. Bibliometric performance indicators can be used to identify the most productive and significant journals, countries, organizations, and individuals. The study makes an effort to identify the important publications in the field; the most often cited works, the top authors, and the top participating nations. The Scopus database is used to get the data. Country network maps and co-authorship network maps are produced using the VOS viewer program. This work advances our understanding of sustainable entrepreneurship and bibliometric methods, which will provide us with a far more complete and trustworthy picture of this field.